PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, STRUKTUR KEPEMILIKAN, PROFITABILITAS, DAN FINANCIAL LEVERAGE TERHADAP PERATAAN LABA (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2016) - Pratiwi, Ananda; Kennedy, Kennedy; Kurnia, Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to analyze the influence of firm size, firm age, ownershipstructure, profitability, and financial leverage to income smoothing in manufacturingcompany listing in Indonesian Stock Exchange. Data is used in this research issecondary data from financial statement (annual report) in Indonesia Stock Exchangeperiod 2014-2016. The sample selection is done with less use of purposive samplingtechniques and criteria used by 51 companies selected.The method used in this study isusing multiple linear regression analysis by using Statistical Product and ServiceSolution (SPSS) ver. 22.0 for windows. The results showed that (1) firm size have notinfluence to income smoothing, level of significance 0,134>0,05, (2) firm age haveinfluence to income smoothing, level of significance 0,046<0,05, (3) ownershipstructure have influence to income smoothing, level of significance 0,030<0,05,(4) profitability have influence to income smoothing, level of significance0,018<0,05, and (5) financial leverage have influence to income smoothing, levelof significance 0,006<0,05.Keywords : Firm Size, Firm Age, Ownership Structure, Profitability, Financial Leverage,and Income Smoothing.